Kolor w przestrzeni miejskiej „Siedem” Davida Finchera - Choczaj, Małgorzata (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2013)
The Colour of Urban Areas in David Fincher’s Seven The city in Seven is full of dark and claustrophobic spaces, dominated by three colors: black, green and red. The significance of these colors is associated with sin: laziness (green), impurity (red) and pride (red, white). Desaturation of color and deep blacks throughout the film are the result of artistic treatments such as flyflashing and bleach-bypass. Color is complemented by light – sometimes minimal, other times quite blinding. The sound of thunder and rain complete the picture of the city as a place of moral decay, where two forces are fighting: light and darkness, purity and sin.